The Teaching of Charles Fourier - Riasanovsky, Nicholas V. (University of California Press, 2020)
Charles Fourier has generally been studied in relation to particular segments of his teaching. Consequently he is known only in one or another of the roles to which biographers or commentators have assigned him, such as that of a social critic, a precursor of Marx, a theoretician of the cooperative movement, or even a progenitor of today's worldwide revolutionary turmoil. Riasanovsky points out that two considerations make an adequate presentation of Fourier's.